Cursory analysis tool for the economic viability of cold thermal energy storage systems - Kueck, Ryan Gregory (Kansas State University, 2019)
Due to large strain placed on the utility grid during times of high commercial and industrial electricity usage, more emphasis is being placed on reducing energy use during these peak times. One of the more popular methods of reducing peak energy usage is the application of cold thermal energy storage (CTES) systems. CTES systems utilize high efficiency chillers to create ice during times of low power consumption or decreased energy cost. This ice is then used to supplement building cooling capacity during peak energy consumption. Although CTES is becoming more popular, frequency of implementation in the United States is still relatively low. Low implementation likely stems from the engineers' unfamiliarity with the system's design and the difficulty of performing the system's life cycle cost analysis. Though research may be done to overcome design unfamiliarity, the significant amount of time required to determine if CTES is economically viable for a project is still an obstacle. Thus, a simple time efficient initial analysis tool is needed. This report introduces an Excel based tool which provides a cursory project specific conservative economic analysis for the viability of CTES. The tool outlined in this report incorporates the many variables which influence CTES design, including the cooling load profile, utility structure, equipment information, and the system configuration of the project. An example analysis demonstrating the capability of the tool is completed at the end of the report. The ability of the tool to quickly provide conservative payback results for CTES systems aids the designer in deciding whether or not to continue with further economic analysis.
Keywords: Cold Thermal Energy Storage; Cursory Analysis Tool; Life Cycle Analysis